2007
DOI: 10.1016/j.brainresbull.2007.03.006
|View full text |Cite
|
Sign up to set email alerts
|

GABAergic mechanisms of the lateral parabrachial nucleus on sodium appetite

Abstract: GABAergic activation in the lateral parabrachial nucleus (LPBN) induces sodium and water intake in satiated and normovolemic rats. In the present study we investigated the effects of GABAA receptor activation in the LPBN on 0.3M NaCl, water, 2% sucrose and food intake in rats submitted to sodium depletion (treatment with the diuretic furosemide subcutaneously+sodium deficient food for 24h), 24h food deprivation or 24 h water deprivation. Male Holtzman rats with bilateral stainless steel cannulas implanted into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
36
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 25 publications
(42 citation statements)
references
References 42 publications
6
36
0
Order By: Relevance
“…Bicuculline and naloxone abolish 0.3 M NaCl and water intake induced respectively by muscimol and ␤-endorphin injected into the LPBN of satiated, fluid replete, rats [20,27,29]. Moxonidine, however, has no effect on sodium or water intake when injected into the LPBN of satiated rats [21].…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…Bicuculline and naloxone abolish 0.3 M NaCl and water intake induced respectively by muscimol and ␤-endorphin injected into the LPBN of satiated, fluid replete, rats [20,27,29]. Moxonidine, however, has no effect on sodium or water intake when injected into the LPBN of satiated rats [21].…”
Section: Discussionmentioning
confidence: 90%
“…Previous studies showed that the treatment with bicuculline (1.6 nmol) into the LPBN abolished the effects of the GABA A agonist muscimol (0.5 nmol) injected into the LPBN on 0.3 M NaCl and water intake in fluid replete rats, in FURO + CAP-treated rats or 24 h sodium depleted rats [27,29]. The injections of saclofen (5 nmol) into the LPBN reduced 0.3 M NaCl intake induced by baclofen (GABA B receptor agonist) injected into the LPBN in satiated rats [30] and naloxone (100 nmol) injected into the LPBN abolished the ingestion of 0.3 M NaCl induced by injections of ␤-endorphin into the LPBN in satiated rats [20].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Signals that influence water and NaCl intake like those from arterial baroreceptors, cardiopulmonary receptors, gustatory receptors and other visceral receptors that reach the NTS ascend to the LPBN (Norgren, 1981;Lança and van der Kooy, 1985;Ciriello et al, 1984;Fulwiler and Saper, 1984;Herbert et al 1990;Jhamandas et al, 1992Jhamandas et al, , 1996. These signals may modulate the activity of LPBN inhibitory mechanisms by releasing different neurotransmitters like serotonin, cholecystokinin, corticotrophin-releasing factor (CRF) and glutamate which increase the inhibitory action, whereas others like GABA, opioids, ATP and noradrenaline reduce the inhibitory action (Andrade et al, 2004Callera et al, 2005;De Gobbi et al, 2009, Gasparini et al, 2009, De Oliveira et al, 2007, 2008Menezes et al, 2011Menezes et al, , 2014Roncari et al, 2014). The deactivation of the inhibitory mechanisms by changing the activity of specific neurotransmitters/receptors in the LPBN increases hypertonic NaCl and/ or water intake induced by different dipsogenic or natriorexigenic stimuli like angiotensin II (ANG II), sodium depletion, water deprivation, central cholinergic activation or even osmoreceptor activation Johnson, 1995, 1998;Menani et al, 1996Menani et al, , 2002Menani et al, , 2014De Luca et al, 2003;Andrade et al, 2004Andrade et al, , 2006De Gobbi et al, 2009;Gasparini et al, 2015b).…”
Section: Introductionmentioning
confidence: 97%